(untitled) (International Journal of Studies in Nursing, 2019)
Background and aim: Improving the eating habits of children is essential to reduce the future burden of non-communicable illnesses. Nutritional diseases affect higher than 30% of school age children. This study aimed to assess the dietary habits and nutritional knowledge among primary school age children in Fayoum Governorate, Egypt. Study design: A cross-sectional descriptive design was utilized. Setting: The study was implemented in three governmental mixed primary schools in EL-Fayoum city; Egypt, that were selected randomly. Sample: Cluster random sample techniques used for selecting of the study group consisted of 300 students aged from 10-12 years for both sexes attending grade five and six. Tools: three tools of data collection consisted of: 1- self-administered questionnaire comprised socio-demographic data of the students and parents, and students’ knowledge about nutrition, 2- the students’ dietary habits as consumption of the breakfast, drinking water, 3- Health assessment sheet to assess the students’ nutritional status including weight, height, BMI, and appearance. The study findings revealed that 69.3% of the study group were underweight, 36.3% were stunted, and 6.7%, 3.3% were overweight and obese respectively. About 45% had fair knowledge while 34% had good knowledge about the nutrition. More than half of the students had unhealthy dietary behavior and appearance. There was a statistically significant difference (P: 0<0.00) between the academic performance of the school children and their HAZ while there was no statistically significant difference between the academic performance of the students and their WAZ (P: 0.264). Conclusions: underweight is highly prevalent among the primary school students followed by stunting. Most of the students had unhealthy dietary habits and unhealthy appearance while around half of them had fair knowledge about nutrition. The current study recommended developing a nutritional health program for primary school children about the proper nutrition.